2012
DOI: 10.1007/s10534-012-9519-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc enhances adiponectin oligomerization to octadecamers but decreases the rate of disulfide bond formation

Abstract: Adiponectin, a hormone secreted from adipocytes, has been shown to protect against development of insulin resistance, ischemia-reperfusion injury, and inflammation. Adiponectin assembles into multiple oligomeric isoforms: trimers, hexamers and several higher molecular weight (HMW) species. Of these, the HMW species are selectively decreased during the onset of type 2 diabetes. Despite the critical role of HMW adiponectin in insulin responsiveness, its assembly process is poorly understood. In this report, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…This indication is consistent with a finding that zinc deficiency augments leptin production in mice supplemented with high fat diet in comparison to the zinc-adequate high-fat fed animals [75]. Moreover, it has been noted that in primary rat adipocytes zinc enhances oligomerization of high-molecular weight adiponectin [78] being more metabolically active in comparison to low-molecular weight adiponectin [79].…”
Section: Tight Association Between Adipose Tissue Trace Element Contesupporting
confidence: 90%
“…This indication is consistent with a finding that zinc deficiency augments leptin production in mice supplemented with high fat diet in comparison to the zinc-adequate high-fat fed animals [75]. Moreover, it has been noted that in primary rat adipocytes zinc enhances oligomerization of high-molecular weight adiponectin [78] being more metabolically active in comparison to low-molecular weight adiponectin [79].…”
Section: Tight Association Between Adipose Tissue Trace Element Contesupporting
confidence: 90%
“…The integrations of Figure 3F showed that the oligomers increased with decrease in ZAG monomer in the case of zinc, but not with barium. These protein-zinc oligomers have been seen previously; the human complement regulator factor H, complement protein C3 [30], and adiponectin also form oligomers in the presence of zinc [31], while zinc induces dimerization of the class II MHC molecule HLA-DR1 in a complex with a hemagglutinin peptide [32].…”
Section: Oligomeric Structure Of Zinc-induced Aggregates Of Zagsupporting
confidence: 64%
“…The reason behind the apparent discrepancy is most probably the differential staining of the oligomers by the Coomassie Brilliant Blue G250 dye. We have observed previously that the staining intensity of adiponectin trimers appeared to be lower than that of the 18mer HMW species in Coomassie dyes (Figure 1 of [35] and Figures 2 and 3 of [36]). Adiponectin is highly negatively charged at neutral pH (calculated pI approximately 5.4) and binds strongly to anion exchange columns.…”
Section: Discussionmentioning
confidence: 77%
“…Approximately 95% of purified adiponectin consists of 18mers with the balance being hexamers. Hexamers were derived from purified 18mers by adjusting the pH to 4 using glycine and re-neutralized to pH 7 using Hepes or PBS at pH 7.4 as previously described [35,36]. …”
Section: Methodsmentioning
confidence: 99%